STUDI TENTANG JENIS KRUSTASEA YANG HIDUP DI KARANG BATU DAN PERANANNYA DALAM EKOSISTEM TERUMBU KARANG - Rianta Pratiwi (Pusat Penelitian Oseanografi LIPI, 2019)
STUDIES ON CRUSTACEANS SPECIES LIVING IN THE CORAL REEF AND THEIR ROLE IN ECOSYSTEM. Crustaceans are one of the most specis invertebrates in coral reefs, comprising approximately 20 % of all invertebrate species. This taxa often found clearly living in coral communities. The order Decapoda is the most common crustaceans observed the coral reefs due to their relatively large size and having bright colours. In addition, decapods contribute in the environmental balance and having important roles in coral reef ecosystem such as defending live coral from predators and helping growth of corals.